The Coalition for Conservation Genetics: Working across organizations to build capacity and achieve change in policy and practice. Issue 4 (8th March 2022) - Kershaw, Francine; Bruford, Michael W.; Funk, W. Chris; Grueber, Catherine E.; Hoban, Sean; Hunter, Margaret E.; Laikre, Linda; MacDonald, Anna J.; Meek, Mariah H.; Mittan, Cinnamon; O'Brien, David; Ogden, Rob; et al.
Abstract: The Coalition for Conservation Genetics (CCG) brings together four eminent organizations with the shared goal of improving the integration of genetic information into conservation policy and practice. We provide a historical context of conservation genetics as a field and reflect on current barriers to conserving genetic diversity, highlighting the need for collaboration across traditional divides, international partnerships, and coordinated advocacy. We then introduce the CCG and illustrate through examples how a coalition approach can leverage complementary expertise and improve the organizational impact at multiple levels. The CCG has proven particularly successful at implementing large synthesis‐type projects, training early‐career scientists, and advising policy makers. Achievements to date highlight the potential for the CCG to make effective contributions to practical conservation policy and management that no one "parent" organization could achieve on its own. Finally, we reflect on the lessons learned through forming the CCG, and our vision for the future.